Prevalence of herpesvirus infections markers at the of kidneys pathology in children - T. V. Barchatova; N. E. Senjagina; V. V. Krasnov (Журнал инфектологии)
The article represents a study of the prevalence of herpesvirus infection markers at different kidney diseases in children. High prevalence of markers of Epstein-Barr virus infection activity in children with acute and chronic glomerulonephritis was detected; acute pyelonephritis in each third child occurs against the background of primary herpes simplex virus-1,2 infections; for children with acute pyelonephritis and acute tubulointerstitial nephritis a high detection rate (>73,5%) of anti-CMV IgG, CMV-viruria (>50%), markers of acute or active CMV infection (in 1/3 – 1/4 of children) are characteristic; at chronic tubulointerstitial nephritis and glomerulonephritis a high prevalence of markers of herpes virus 6 infection activity was observed; children with different forms of acute and chronic renal pathology demonstrate high frequency of EBV, CMV, herpesvirus-6-viruria (1/3 –of patients).